The relationship of school climate, teacher defending and friends on students' perceptions of bullying in high school. (January 2018) - Mucherah, Winnie; Finch, Holmes; White, Taylor; Thomas, Kendra
Abstract: The purpose of this study was to examine the relationship of school climate, teacher defending, and friends on bullying and victimization. Participants were 2273 high school students from 3 public schools (an all girls, all boys boarding, and a co-ed day) in Kenya. A structural equation model was used to examine relationships between school climate, teacher behavior toward bullying, and student demographic characteristics, and bullying. Results revealed that a positive school climate was associated with less bullying behavior and victimization. In addition, when students reported that teachers stop bullying by students, bullying behavior and victimization scores were lower. Contrary to previous research these results showed that residents of a boys only boarding school were less likely to report bullying behavior than residents of an all girls school, or students at a co-educational institution. Furthermore, there were no differences in bullying behavior or victimization by gender or grade level. Implications of these results are discussed.